Caring for human trafficking victims: A description and rationale for the Medical Safe Haven model in family medicine residency clinics. (September 2019) - Chambers, Ronald
Human trafficking is a growing public health issue. As we understand more about the prevalence of persons experiencing trafficking accessing clinical services and their unique healthcare needs, we recognize the need for programs dedicated to creating a safe environment to ensure victims and survivors have equitable, sustainable access to the physical, mental, and psychosocial care they require. Healthcare providers are often a first line of care for persons experiencing trafficking and represent a significant opportunity to positively impact outcomes in terms of health, overall quality of life, and reintegration into society. Here we discuss how persons experiencing trafficking present in the clinic, including survivors' reported experiences with healthcare providers, how to identify victims, and why it is important to do so appropriately in a trauma-informed manner. We then describe key characteristics of a "Medical Safe Haven" clinic, an umbrella term used to describe clinics providing longitudinal care for patients who have been trafficked using validated victim-centered trauma-informed care techniques and incorporating survivor-informed practices. Medical Safe Haven clinics coordinate care with local community agencies, provide training for healthcare providers, and ensure longitudinal, comprehensive care by mitigating barriers to access, reducing risk of re-traumatization, and preventing failure of victim rehabilitation. We conclude with recommendations for next steps in evaluation and dissemination of this model of care.